PENENTUAN JUMLAH PERSEDIAAN BAHAN BAKU PRODUK TEMPE DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) - Noer Novijanto (JURNAL AGROTEKNOLOGI, 2010)
Tempe is one of traditional and most delicious Indonesian food. Tempe is made up of soybean which is fermented to become tempe. Therefore management activities and stock controlling is very important for the company because its impact to the performance especially financially. Those activities often creating problem if not well manage, such as over stock or even creating stock out.This research was conducted to know the optimum soybean stock properly available by using economic order of quantity (EOQ) for a period of time. Result showed that before applying of EOQ the need for raw material for the production period of April 2010 was 2297 kg of soybean, while amount of raw material, while amount of raw material provided by that home industry or quantity of material ordered was 2655.8 kg. However, after applying EOQ it was known that the most economical stock ordered and frequent of stock. Stock ordered was 126,23 kg for 21 times of stock ordered in April 2010. Therefore, total cost for ordering raw material was reduced. Total cost by using EOQ was Rp 6,350.- in one period time of ordering, whilst without using EOQ was Rp 67,000.- causing in the reduction ordering cost in April 2010 Rp 134,650.--.Keywords: economic order of quantity, inventory, tempe